Facts About Vitamin B6 - Anne Kendall (EDIS)
Vitamin B6, also called pyridoxine, is a water-soluble vitamin needed to break down the protein we eat. This vitamin is used by our bodies to make important proteins, and it helps our muscles use energy. It also helps make brain chemicals that tell the systems in our bodies what to do. This 2-page fact sheet was written by Anne Kendall and published by the UF Department of Family Youth and Community Sciences, July 2013.